The Influence Of Generation Z Participation In Implementing Events In Tabanan District Tourism Villages - Sri Candrawati, Anak Agung Ketut; Prianta, Putu Agung; Wahyuni, A. A. Nyoman Sri (Politeknik Internasional Bali, 2024)
Tabanan Regency has 133 villages, 28 of which have become tourist villages in 2023. Several tourist villages hold promotional events through social media. Generation Z uses social media the most, but tourist village managers have not involved Generation Z much, including in organizing events. The purpose of this study was to analyze the participation and influence of generation Z in implementing events in Tabanan Regency Tourist Villages. Mixed research methods. Primary and secondary data collection techniques were carried out by means of observation, interviews, questionnaires, literature studies and document studies. The analysis technique used the Statistical Test t (t-test). This research theory, the theory of participation, classifies participation into 2 based on its involvement, namely direct participation and indirect participation. In conclusion, that the participation of generation Z (aged 11-26 years) in organizing events in Tabanan Regency Tourist Villages is still not optimal, namely 12.4%, while the results of the T test concluded that Gen Z partially has a significant influence on organizing events in Tabanan Regency tourist villages.